The development of PISA-like problems using immunity context during pandemic - Ayu Luviyanti Tanjung; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Jurnal Elemen, 2023)
The quality of education in Indonesia has yet to be able to balance the importance of mathematical literacy. It can be seen from the OECD's data that a mathematical literacy achievement score of 379 shows that the literacy ability of Indonesian students is still low. This research aimed to develop PISA-like problems that are valid and practical and potentially affect mathematical literacy skills using the context of immunity during a pandemic. This research used the Inquiry-Based Learning (IBL) model in small group and field test stages. The subjects in this study were eighth-grade students aged 13-15. The data were analyzed qualitatively through observations, interviews, and tests. This study produces one unit of sharing task and jumping task and three evaluation problems with characteristics of the content used, name change and relationship, and personal and social contexts. Levels by the framework PISA 2022, namely levels 3, 4, and 5, are process competence and mathematical literacy skills. Using language following language standards can be understood and interpreted well by students. Thus, this research produces the developed PISA-like problems that are valid and practical and potentially affect mathematical literacy skills and life skills in dealing with the pandemic.